Association of adalimumab trough concentrations and treatment response in patients with juvenile idiopathic arthritis. (20th April 2021) - Doeleman, Martijn J H; de Roock, Sytze; El Amrani, Mohsin; van Maarseveen, Erik M; Wulffraat, Nico M; Swart, Joost F
Abstract: Objective: The objective of this study was to assess the relationship between adalimumab trough concentrations and treatment response in paediatric patients with JIA. Methods: This was a monocentric cohort study of JIA patients treated with adalimumab. Clinical data and samples were collected during routine follow-up. Adalimumab trough concentrations were quantified by a novel liquid chromatography–tandem mass spectrometry assay. Anti-adalimumab antibodies were measured in samples with trough concentrations of ≤5mg/l. Disease activity was evaluated using the clinical Juvenile Arthritis DAS with 71-joint count (cJADAS71). Response to adalimumab was defined according to recent international treat-to-target guidelines. Results: A total of 35 adalimumab trough samples were available from 34 paediatric patients with JIA. Although there was no significant difference in adalimumab dose, trough concentrations were significantly lower in patients with secondary failure [median 1.0 mg/l; interquartile range (IQR) 1.0–5.3] compared with patients with primary failure (median 13.97 mg/l; IQR 11.81–16.67) or an adequate response (median 14.94 mg/l; IQR 10.31–16.19) to adalimumab. Conclusion: Adalimumab trough concentrations were significantly lower in JIA patients with secondary failure compared with patients with primary failure or an adequate response to adalimumab. Our results suggest that trough concentration measurements could identify JIA patients who require increased adalimumab doses to achieve or maintain therapeutic drug concentrations.